Kajian Kultur Religius Terhadap Pemahaman Leluhur Orang Minahasa - Maweikere, Ravindo Johnny; Tewu, Matulandi Arthur (Educatio Christi, 2024)
This article discusses "Religious Culture Study of Views About Minahasan Ancestors in the GMIM Elim Suluan Congregation, Tomohon Lima Region." This congregation is located in Suluan Village, Tombulu District, Minahasa Regency, North Sulawesi Province. The life of the Elim Suluan Congregation is still very much influenced by the mixture of Minahasa cultural traditions and customs which continues to develop to this day. The Suluan context where society is increasingly open to modern progress through technology, information and transportation which can be felt means that the existence of traditions in culture is starting to be eroded, so Based on the existing reality, it is deemed necessary to provide understanding to the congregation, so that the congregation understands more deeply that knowing about the ancestors of the Minahasa people and their life values is very important and influences the continuity of church life within the congregation.